Scientific Certitude - Braude, Stephen (Journal of Scientific Exploration, 2020)
I’ve been both fascinated and distressed by the arguments raging over how best to respond to the covid-19 pandemic. In particular, I’ve been struck by the way people claim scientific authority for their confident assurances of what needs to be done. And I’m especially intrigued by the scorn they often lavish on those who hold differing views on what science is telling us. The heat generated by the resulting debates is strikingly similar to the heat generated by debates over the science connected with human-caused climate change. And in both cases, the disputants too often presuppose indefensibly naïve views about scientific authority and certitude, apparently unaware that even the allegedly most obvious logical truths lack the certainty attributed to scientific authority in these debates. As a rule, I dislike re-circulating my Editorials, but I think it’s time to resurrect one (modestly tweaked) from a few years ago, addressing precisely this issue (Vol. 31, No. 3, pp. 379–386, 2017). …………………………………… “Man is a rational animal who always loses his temper when he is called upon to act in accordance with the dictates of reason.” --Oscar Wilde I’ve often noticed how debates within the SSE community sometimes parallel debates in the political arena, perhaps especially with respect to the passion they elicit and the intolerance and condescension sometimes lavished on members of the “opposition.” Occasionally, of course, the debates in the SSE are nearly indistinguishable from those in the political arena—say, over the evidence for human-caused climate change. But what I find most striking is how the passion, intolerance, etc.—perhaps most often displayed by those defending whatever the “received” view happens to be—betrays either a surprising ignorance or else a seemingly convenient lapse of memory, one that probably wouldn’t appear in less emotionally-charged contexts. What impassioned partisans tend to ignore or forget concerns (a) the tentative nature of both scientific pronouncements and knowledge claims generally (including matters ostensibly much more secure than those under debate), as well as (b) the extensive network of assumptions on which every knowledge claim rests. So I’d like to offer what I hope will be a perspective-enhancer, concerning how even our allegedly most secure and fundamental pieces of a priori knowledge are themselves open to reasonable debate. A widespread, but naïve, view of logic is that no rational person could doubt its elementary laws. But that bit of popular “wisdom” is demonstrably false. And if that’s the case, then so much the worse for the degree of certitude we can expect in more controversial arenas. Let me illustrate with a few examples.[1] [1] I’m indebted to Aune, 1970 for much of what follows.